Analysis and collaboration lays the foundation for food system improvements in Ethiopia - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The first step toward identifying ways to improve something is to understand the current situation. In 2018, A4NH researchers completed an in-depth analysis of Ethiopian food systems to determine what and where research is needed. This has evolved into a food systems research agenda for Ethiopia. In 2018, Flagship 1 researchers with national stakeholders started implementing the agenda through activities like development of food based dietary guidelines and embedding evidence-based activities in efforts to operationalize the National Nutrition-Sensitive Agriculture Strategy.